Effectiveness of Ginger Herbal Remedies, Ginger Boreh, and Infrared Therapy in Increasing Breast Milk Production - Diniyati, Lena Sri; Rahmawati, Rahmawati (Genius Journal, 2024)
Introduction: The high incidence of stunting and the low prevalence of exclusive breastfeeding in Indonesia are primarily caused by insufficient breast milk production. Objective: This study aims to determine the effectiveness of ginger herbal remedies, ginger boreh, and infrared therapy in increasing breast milk production in breastfeeding mothers. Methods: This research utilized a quantitative experimental method. A pre-experimental design with a one-group pre-test and post-test approach was employed. The subjects were observed before the intervention and re-observed after the intervention. The study population consisted of postpartum mothers in the working area of Cisarua. The sample included 30 breastfeeding mothers, selected through purposive sampling. The sample was filtered from the population based on inclusion and exclusion criteria. Results: Statistical analysis using the Wilcoxon test revealed a significant p-value of 0.000, which is smaller than the significance threshold (p-value = 0.05 > 0.000). Thus, it can be concluded that the administration of ginger herbal remedies, ginger boreh, and infrared therapy is effective in increasing breast milk production in postpartum mothers. Conclusion: This study can serve as a therapy in maternal breastfeeding care and as a foundation for future research development, focusing on method enhancements or innovative approaches.